THE POSITION AND AUTHORITY OF CONSTITUTIONAL COURT IN CONSTITUTIONAL SYSTEM OF THE REPUBLIC OF INDONESIA - AD. Basniwati (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
According to institutional or organization system the existence of constitutional court as one of judicial body is not a subordinate of supreme courts other judicial body. This is mean; there are dual highest judicial body among judicial authorities,  which are the supreme court and constitutional court. The arising problem is related to the function and position of constitutional court  in constitutional system of the people of Indonesia. Standing position of constitutional court as a highest judicial body implicates to the Supreme Court. Where  before the formation of constitutional court,  supreme court was the highest judicial body which coordinates all judicial power,  afterward,  there is one judicial body which stand equally to it,  that is constitutional court. Moreover,  through its constitutional authority.  constitutional court hold the authority implementation of Supreme Court to examine regulation which hierarchy level lower than the law against the valid law.Keywords : Constitutional court